2015
DOI: 10.1002/mds.26417
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative susceptibility mapping of the midbrain in Parkinson's disease

Abstract: Background Parkinson’s disease (PD) is marked pathologically by dopamine neuron loss and iron overload in the substantia nigra pars compacta. Midbrain iron content is reported to be increased in PD based on magnetic resonance imaging (MRI) R2* changes. Because quantitative susceptibility mapping is a novel MRI approach to measure iron content, we compared it with R2* for assessing midbrain changes in PD. Methods Quantitative susceptibility mapping and R2* maps were obtained from 47 PD patients and 47 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
161
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(184 citation statements)
references
References 39 publications
19
161
2
2
Order By: Relevance
“…The voxel-based morphology analysis by Du et al (132) elegantly demonstrates selective SNc iron increase in perfect concordance with post mortem histology, underscoring the potential of QSM as a biophysical marker for therapeutic effects in clinical trials. While these studies may provide little direct value for current symptomatic levodopa medication of PD patients, QSM could be an essential imaging tool for DBS and iron-chelating therapy.…”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 84%
See 1 more Smart Citation
“…The voxel-based morphology analysis by Du et al (132) elegantly demonstrates selective SNc iron increase in perfect concordance with post mortem histology, underscoring the potential of QSM as a biophysical marker for therapeutic effects in clinical trials. While these studies may provide little direct value for current symptomatic levodopa medication of PD patients, QSM could be an essential imaging tool for DBS and iron-chelating therapy.…”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 84%
“…Devos, et al have recently reported very encouraging results showing that DFP improves PD motor performance and reduces nigral R2* values on GRE MRI, suggesting that DFP can be the first disease-modifying therapy for PD (127). Because QSM is superior to R2* for evaluating nigral iron (131,132,134,135,145), an important potential application of QSM in PD is to measure DFP's effectiveness of target-engagement in clinical trials.…”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 99%
“…These can be better observed in susceptibility maps than in simultaneously acquired R 2 * maps (Du et al, 2015;Murakami et al, 2015). This points towards either using multi-echo protocols covering a range of echo times up to 30ms, which will be sufficiently robust to compute R 2 * and susceptibility maps of deep gray matter regions, or single echo acquisitions with a TE~15-20ms and low BW to maximize SNR, and be able to compute susceptibility maps.…”
Section: Study Of Neurodegenerative Diseases and Agingmentioning
confidence: 96%
“…Conventionally, LIC is measured using either R2 or R2* mapping based methods. It has been shown that R2* has superior sensitivity to changes in cerebral iron content than R2 (36), and QSM has even better sensitivity than R2* (10,37,38). The great potential of QSM has already been demonstrated in a recent study, in which the conventional QSM algorithms were adapted for liver iron quantification.…”
Section: Discussionmentioning
confidence: 99%